(untitled) (Detroit, 2006)
This title is one of a planned 10-book Social Issues Primary Resources Collection covering topics such as human rights, crime, health, gender, immigration, and family. Each volume will showcase 175 primary sources including speeches, legislation, letters, magazine articles, songs, photos, and pictures. Typical examples of the sources chosen for inclusion in Terrorism are "The Case against the Reds," "Letter from Timothy McVeigh," "TWA Flight 847 Hijacking," "Eulogy for Yitzhak Rabin," "How Did Eric Rudolph Survive?" and "USA PATRIOT Act." Sources are arranged in thematic chapters such as "Insurgent f Terrorism," "Religious Terrorism," and "Counterterrorism."
Keywords: Terrorism,Sự khủng bố; History,Lịch sử